2006
DOI: 10.1080/10428190600724928
|View full text |Cite
|
Sign up to set email alerts
|

Anticipation in families with Hodgkin's and non-Hodgkin's lymphoma in their pedigree

Abstract: Anticipation is an earlier onset and/or increasing severity in successive generations. This study was conducted to determine whether anticipation occurs in families that exhibit both Hodgkin's (HD) and non-Hodgkin's (NHL) lymphoma in their pedigrees. Nine published reports of multi-generational lymphoma and 33 previously unreported families with both lymphomas were analysed for evidence of anticipation. The difference between age at onset for each affected related pair was tested against the null hypothesis th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
5
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(6 citation statements)
references
References 46 publications
(56 reference statements)
1
5
0
Order By: Relevance
“…Most types of familial lymphoid malignancies occurred, on average, at a substantially younger age than sporadic cases, even after controlling for age incidence patterns, sex, and subtype. The younger onset of familial cases is consistent with other studies [4,5,[8][9][10]. We also observed anticipation across 3 or more generations of lymphoid cancer families for NHL, DLBCL, LPL/WM, CLL and HL cases.…”
supporting
confidence: 92%
See 1 more Smart Citation
“…Most types of familial lymphoid malignancies occurred, on average, at a substantially younger age than sporadic cases, even after controlling for age incidence patterns, sex, and subtype. The younger onset of familial cases is consistent with other studies [4,5,[8][9][10]. We also observed anticipation across 3 or more generations of lymphoid cancer families for NHL, DLBCL, LPL/WM, CLL and HL cases.…”
supporting
confidence: 92%
“…Anticipation is an inheritance pattern where disease severity increases and/or age of onset decreases in successive generations. It has been documented in neurodegenerative disorders [1,2], autoimmune diseases [2], and several cancers, including familial leukemias and lymphomas [2][3][4][5][6][7][8][9][10]. In neurodegenerative disorders such as Huntington's disease, genetic anticipation is due to the expansion of trinucleotide repeat sequences [1]; in cancer, the molecular mechanism remains unknown.…”
mentioning
confidence: 99%
“…8,15,[28][29][30] In other families, multiple generations are affected with LN, 15,30,31 implying the transmission of highly penetrant, possibly dominant, pleiotropic genetic traits. In a subset of families, there is evidence for genetic anticipation, where the age of diagnosis in subsequent generations is successively lower, 19,32 indicative of a non-Mendelian mechanism. In this study, there were few siblings affected with cancer and none affected with HL; thus, most of the observed LN aggregation was attributable to affected case parents (Supporting Information Table S5).…”
Section: Discussionmentioning
confidence: 99%
“…Anticipation (i.e. earlier onset and/or increasing severity in successive generations) occurs in families that exhibit both HL and NHL and it has been suggested that both neoplasms may have a common genetic basis 152. The relative risk of the development of HL increases approximately 100-fold in monozygous twins 153, 154 and seven-fold in siblings of patients less than 45 years of age 155.…”
Section: Etiologic Considerationsmentioning
confidence: 99%